Updating the goal model with user reviews for the evolution of an app. Issue 8 (27th February 2020) - Gao, Shanquan; Liu, Lei; Liu, Yuzhou; Liu, Huaxiao; Wang, Yihui
Abstract: Goal model is an important model in requirements engineering, and it can describe features and their relationships for supporting the development of apps. Since an app evolves continually, the goal model also needs to be updated with new requirements to guide the whole process. As the feedback of users, reviews provide an abundant resource of user requirements for updating the goal model. In this paper, we propose an approach to help developers (a) analyze reviews to gain the information of user requirements by training a classifier and defining keyword‐based linguistic rules as well as grammar‐based rules and (b) update the goal model with the extracted information, including improving existing goals and extending the model with new goals. In addition, we design a framework to represent results so that they can be understood by developers easily. According to our experiments based on the data in Google Play, the F‐measure of classifier on reviews can reach 75.76%, and the average precision for extracting requirements‐related information from reviews is 84.04%, then we can map the information to goals with the F‐measure of 70.21%. Furthermore, the survey on 22 developers shows that the information provided by us is useful for updating the goal model. Abstract : The approach combines review analysis with goal model, and it can help developers gain user requirements from reviews by training a classifier and defining keyword‐based linguistic rules as well as grammar‐based rules